Advances in the molecular characterization of multiple myeloma and mechanism of therapeutic resistance - Mejia Saldarriaga, Mateo; Darwiche, Walaa; Jayabalan, David; Monge, Jorge; Rosenbaum, Cara; Pearse, Roger N.; Niesvizky, Ruben; Bustoros, Mark (Frontiers in Oncology, 2022)
Recent insight in the genomic landscape of newly diagnosed multiple myeloma (NDMM) and its precursor conditions, monoclonal gammopathy of uncertain significance (MGUS), and smoldering myeloma have allowed the identification of patients with precursor conditions with a high risk of progression. These cases with “progressor” MGUS/SMM have a higher average mutation burden, have higher rates of mutations in specific genes such as MAPK, DNA repair, MYC, DIS3, and are enriched for specific mutational signatures when compared to non-progressors and are comparable to those found in NDMM. The highly preserved clonal heterogeneity seen upon progression of SMM, combined with the importance of these early variables, suggests that the identification of progressors based on these findings could complement and enhance the currently available clinical models based on tumor burden. Mechanisms leading to relapse/refractory multiple myeloma (RRMM) are of clinical interest given worse overall survival in this population. An Increased mutational burden is seen in patients with RRMM when compared to NDMM, however, there is evidence of branching evolution with many of these mutations being present at the subclonal level. Likewise, alterations in proteins associated with proteosome inhibitor and immunomodulatory drugs activity could partially explain clinical resistance to these agents. Evidence of chromosomal events leading to copy number changes is seen, with the presence of TP53 deletion, mutation, or a combination of both being present in many cases. Additional chromosomal events such as 1q gain and amplification may also interact and lead to resistance.